2016
DOI: 10.3892/mmr.2016.5353
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic death induced by thermo-chemotherapy in gastric cancer cells results from the reactive oxygen species pathway

Abstract: Gastric cancer is the third leading type of cancer and has the third leading cancer‑associated mortality in China. The mechanism of thermo‑chemotherapy in gastric cancer cells remains to be elucidated. The present study aimed to investigate the role of autophagic cell death in the thermo‑chemotherapy of gastric cancer. The current study included four groups: An empty control group, a hyperthermia group, a chemotherapy (oxaliplatin) group, and a thermo‑chemotherapy group. Cell viability was analyzed by the MTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It has been reported that ROS acted on the complex formed by Beclin-1 and anti-apoptotic Bcl-2 homologs such as Bcl-2 and Bcl-xL. Moreover, this complex repressed the pro-autophagic activity of Beclin-1 and ROS could induce the dissociation of autophagy molecules Beclin 1 and Bcl-2, thus activating the Beclin1-induced autophagy pathway, increasing the expression of LC3-II, thereby initiating autophagy-associated pathways [ 49 , 50 ]. ROS is also reported to upregulate the activity of HIF1-α which facilitates the activation of the HIF1-α/BNIP3/Beclin1 autophagy signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ROS acted on the complex formed by Beclin-1 and anti-apoptotic Bcl-2 homologs such as Bcl-2 and Bcl-xL. Moreover, this complex repressed the pro-autophagic activity of Beclin-1 and ROS could induce the dissociation of autophagy molecules Beclin 1 and Bcl-2, thus activating the Beclin1-induced autophagy pathway, increasing the expression of LC3-II, thereby initiating autophagy-associated pathways [ 49 , 50 ]. ROS is also reported to upregulate the activity of HIF1-α which facilitates the activation of the HIF1-α/BNIP3/Beclin1 autophagy signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ROS acted on the complex formed by Beclin-1 and anti-apoptotic Bcl-2 homologs such as Bcl-2 and Bcl-xL. Moreover, this complex repressed the pro-autophagic activity of Beclin-1 and ROS could induce the dissociation of autophagy molecules Beclin 1 and Bcl-2, thus activating the Beclin1-induced autophagy pathway, increasing the expression of LC3-II, thereby initiating autophagy-associated pathways [48,49]. In addition, ROS is also reported to upregulate the activity of HIF1-α, and some scholars have also shown that the expression and activity of HIF-1a is not only induced in response to limited oxygen supply, but it is also regulated through related signaling pathways, including the extracellular signal-regulated kinase (ERK) [50] and the protein kinase B (AKT) [51] pathway, and hyperthermia promoted the expression of HIF-1α by activating phosphatidylinositol 3-kinase(PI3K)…”
Section: Discussionmentioning
confidence: 99%